Javanese Speaker’s Attitude Toward Their Speech Levels In Desa Danau Sijabut - Affiah, Hajar (L'Geneus : The Journal Language Generations of Intellectual Society, 2020)
This study deals with Javanese speaker’s attitude toward their speech levels in Desa Danau Sijabut. It aims at finding out what the characteristics of Javanese speaker’s attitude are when they use the dominant speech level, how the linguistic realizations of Javanese speaker’s attitude toward their speech levels is and why they have such attitudes toward their speech level like the way they do. This study was conducted in qualitative research of which design was descriptive a case study. The sources of data for this study were 20 Javanese speakers of second generation of migration who live in Desa Danau Sijabut; meanwhile the data were taken from the transcripts of Javanese utterances spoken during the Javanese speakers communicate in their daily life. The data were analyzed by using Interactive Model by Miles, Huberman, and Saldana (2014). To find out the characteristics of Javanese speaker’s attitude, the researcher used theory of Garvin & Mathiot (1968), to see the realizations of Javanese speech levels, the researcher used theory of Rahardi (2001), while to find out the reasons why the Javanese speakers have such attitudes like the way they do, besides used theory of Subroto (2014), researcher also asked the respondents more deeply. Based on the data analysis, the first finding shows that the characteristics of Javanese speaker’s attitude when they used the dominant speech level is language pride. In which they used Javanese language based on the speech levels in formal and informal situation to show their identity as Javanese. The second finding, it was found the Javanese speakers in Desa Danau Sijabut realized their attitudes in the several domains, such as: use Ngoko speech level at home, use Ngoko and Madya at neighborhood, used Ngoko and Indonesian language at work place. In this case, they were speak based on the relationship between speakers and participants. And as the third findings, it was found the Javanese speakers in Desa Danau Sijabut have such attitudes toward the Javanese speech levels because of some reasons. Firstly, they use Ngoko to make communication clearly and easier to understand what their partner said during they have a communication. Secondly, they use Madya when to talk a secret one to their speaker partner without afraid will be known by another people of what they are talking about. Besides, those become their habit in using speech level and aware to the rules of Javanese speech levels.